The Relationship Between Parental Images and Ministerial Job Satisfaction Among Anglican Clergymen in England - Turton, Douglas W. (Research in the social scientific study of religion, 2006)
A sample of 1,276 Anglican parochial clergymen in England completed a modified form of the Glass Ministerial Job Satisfaction Scale, a self-reported scale on parental images, and the short-form Revised Eysenck Personality Questionnaire. The aim of the present study was to test empirically the relationship between parental images and current levels of ministerial job satisfaction among clergymen. Given the fact that previous studies have demonstrated the relationship between aspects of clergy work-related psychological health and individual differences in personality, the present study also included an established measure of personality. The data demonstrate that negative parental images are a significant predictor of poor ministerial job satisfaction, after controlling for individual differences in age and in personality.